Little evidence that farmers should consider abundance or diversity of arbuscular mycorrhizal fungi when managing crops - Ryan, Megan H.; Graham, James H. (The New phytologist, 2018)
Arbuscular mycorrhizal fungi (AMF) are ubiquitous in agroecosystems and often stated to be critical for crop yield and agroecosystem sustainability. However, should farmers modify management to enhance the abundance and diversity of AMF? We address this question with a focus on field experiments that manipulated colonisation by indigenous AMF and report crop yield, or investigated community structure and diversity of AMF. We find that the literature presents an overly optimistic view of the importance of AMF in crop yield due, in part, to flawed methodology in field experiments. A small body of rigorous research only sometimes reports a positive impact of high colonisation on crop yield, even under phosphorus limitation. We suggest that studies vary due to the interaction of environment and genotype (crop and mycorrhizal fungal). We also find that the literature can be overly pessimistic about the impact of some common agricultural practices on mycorrhizal fungal communities and that interactions between AMF and soil microbes are complex and poorly understood. We provide a template for future field experiments and a list of research priorities, including phosphorus-efficient agroecosystems. However, we conclude that management of AMF by farmers will not be warranted until benefits are demonstrated at the field scale under prescribed agronomic management.